Damage tolerance of CFRP airframe bolted joints in bearing, following bolt pull-through failure. (15th March 2020) - Giannopoulos, Ioannis K.; Grafton, Kaelan; Guo, Shijun; Smith, Howard
Abstract: The experimental study presented herein, investigated the residual strength of bolted joints on Carbon Fiber Reinforced Polymer (CFRP) airframe structures within the context of structural damage tolerance and airworthiness regulations. The damage scenario assumed, subjected a series of bolted joint CFRP laminate specimens to quasi-static bearing loading, following bolt pull-through failure events of different magnitude. Representative CFRP laminate specimens manufactured from AS7/8552 carbon fiber/epoxy matrix system were artificially damaged under bolt pull-through loading, following the herein proposed modifications to the current pull-through ASTM testing procedure. The specimens were subsequently tested in static bearing loading for examining the specimen residual bearing strength. The residual joint bearing strength was related to the displacement travelled passed the initial failure stage in pull-through mode and was measured up to a maximum of a 13% decrease for the tested samples and the maximum damage imposed. The study explored the safe utilization of bolted joints at higher operating loading levels, within the context of the current airworthiness regulations. The inherent damage arrest features of the joints were highlighted. The study concluded with comments and suggestions on the expansion of the current utilization spectrum of damaged bolted joints from pull-through loading in airframe design, bound by the current airworthiness certification requirements.